Molecular Mechanism of Antioxidant and Anti-Inflammatory Effects of Omega-3 Fatty Acids in Perilla Seed Oil and Rosmarinic Acid Rich Fraction Extracted from Perilla Seed Meal on TNF-_ Induced A549 Lung Adenocarcinoma Cells - Payungsak Tantipaiboonwong; Wittaya Chaiwangyen; Maitree Suttajit; Napapan Kangwan; Sirichat Kaowinn; Chakkrit Khanaree; Wanisa Punfa; Komsak Pintha (My University, 2021)
Industrially, after the removal of oil from perilla seeds (PS) by screw-type compression, the large quantities of residual perilla seed meal (PSM) becomes non-valuable waste. Therefore, to increase the health value and price of PS and PSM, we focused on the biological effects of perilla seed oil (PSO) and rosmarinic acid-rich fraction (RA-RF) extracted from PSM for their role in preventing oxidative stress and inflammation caused by TNF-α exposure in an A549 lung adenocarcinoma culture model. The A549 cells were pretreated with PSO or RA-RF and followed by TNF-α treatment. We found that PSO and RA-RF were not toxic to TNF-α-induced A549 cells. Both extracts significantly decreased the generation of reactive oxygen species (ROS) in this cell line. The mRNA expression levels of IL-1β, IL-6, IL-8, TNF-α, and COX-2 were significantly decreased by the treatment of PSO and RA-RF. The Western blot indicated that the expression of MnSOD, FOXO1, and NF-κB and phosphorylation of JNK were also significantly diminished by PSO and RA-RF treatment. The results demonstrated that PSO and RA-RF act as antioxidants to scavenge TNF-α induced ROS levels, resulting in decreased the expression of MnSOD, FOXO1, NF-κB and JNK signaling pathway in a human lung cell culture exposed to TNF-α.
Keywords: Rosmarinic acid; Perilla; Perilla frutescens; Natural Products and Biological Research